TBIO-21. ANALYSIS OF PAIRED BRAFV600E MUTANT GLIOMA PATIENT SAMPLES IDENTIFIES NOVEL RESISTANCE MECHANISMS TO TARGETED BRAF INHIBITION. Issue 2 (22nd June 2018) - Levy, Jean Mulcahy; Sanford, Bridget; Morin, Andrew; Green, Adam; Flannery, Patrick; Jones, Kenneth; Banerjee, Anurhada; Nazemi, Kellie; Samuel, David; Kilburn, Lindsay; Solomon, David; Nicolaides, Theodore
Abstract: BRAF V600E mutations occur in a variety of gliomas and BRAF V600E targeted therapies have provided new treatment options. Trials in melanoma and colorectal cancer, as well as early results in CNS tumors, indicate a high risk for the development of resistance. To date there is little data available for resistance mechanisms in glioma patients treated with BRAF V600E inhibition. To identify molecular and pathway alterations driving resistance, we performed targeted next-generation DNA sequencing, RNA sequencing, and Ingenuity Pathway Analysis (IPA) on paired pre-treatment and post-resistance primary pediatric glioma samples (n=10) and cell lines (n=2). Unique genetic alterations likely driving tumor recurrence and resistance to BRAF inhibition were identified. Novel mutations in post-resistance samples included a de novo mutation in the CBL gene within the RING finger domain of the E3 ubiquitin ligase protein that has been recurrently found in myeloid neoplasms, a frameshift mutation in the RB1 tumor suppressor gene, and a nonsense mutation in ERRFI1, which encodes a negative regulator of EGFR signaling. IPA analysis demonstrated significant pathway activation differences in post-resistance samples. There was a predominance of upregulated receptor tyrosine kinase pathways including EGFR, NTRK2, TGFB1, estrogen receptor, ERBB2, and PI3K. Expected up-regulation of MEK, MAPK1, MAP2k1 and ERK1/2 pathways were found. The altered pathways were unique for each paired set. These data suggest that pediatric gliomas develop resistance to BRAF inhibition using a multitude of genetic and transcriptional mechanisms that are potentially distinct in each tumor, and with novel resistance mutations not found in resistant melanoma or colorectal cancers.